The Effect of Educational Program for Forms of Play on the Development of Some Visual, Motor abilities and Offensive Skills Performance Accuracy In Young Volleyball Players - Riyadh, Wesam (Journal of Physical Education, 2018)
The Effect of Educational Program for Forms of Play on the Development of Some Visual, Motor abilities and Offensive Skills Performance Accuracy In Young Volleyball PlayersThe problem of the research lies in players’ weakness in visual and motor abilities that negatively reflect offensive skills’ performance in volleyball.  The researcher aimed at designing an educational program with the forms of play to develop some visual and motor abilities and performance of offensive skills in junior volleyball as well as identifying the effect of this program. The researcher hypothesized positive effect of the educational program on the forms of playing on the development of some visual and motor abilities and the accuracy of offensive skills’ performance in the post-test and in favor of the experimental group. The researcher used the experimental method. The sample were (16) players of Al Hashimia Club for the season 2018. The data was collected and treated using proper statistical operation to conclude that the educational program positively affected the development of some visual and motor abilities and accuracy of skills performance. Finally the researcher recommended paying attention to using educational program according to play forms in all educational session for compound skills in youth volleyball.